Curating conclusions in 'Among Us': Collaborative Twitter fiction and the implied author. Issue 1 (1st September 2018) - Segar, Emma
This article uses the author's experiences of preparing and curating 'Among Us', a 24-hour collaborative Twitter fiction, to examine the role of creators and contributors in producing a consistent narrative with a coherent thematic focus. It draws upon the concept of the 'implied author' as it applies to blog fiction and other forms of networked digital storytelling. It outlines the processes that brought participants together, and explores the ways in which they sought out ideological suggestions in the curator's prompts, predicting, supporting, resisting or commandeering these in their contributions in order to ultimately collaborate on the conclusions and act as a single, recognizable 'implied author'.